Moral Values and Struggle in the Story of Saba Nan Aluih, From the Region of Padang Tarok Baso, Agam - Abdul Aziz Aziz (Universitas Ahmad Dahlan, 2021)
The values ​​of struggle and moral values ​​in literature are dependent on each other. Literature is strongly influenced by the values ​​of struggle and moral values, so that everything contained in morals and struggles is reflected in literature. Thus, literary works can be approached using the values ​​of struggle and moral values. The problem of this research is about the value of struggle and moral values ​​contained in the folklore of Saba Nan Aluih. The purpose of this study is to describe the description of the values ​​of struggle and moral values ​​in the folklore of Saba Nan Aluih. The data of this study is a description of the values ​​of struggle and moral values ​​in the folklore of Saba Nan Aluih. The method used is descriptive method with qualitative analysis by describing the description of the values ​​of struggle and moral values ​​in the folklore of Saba Nan Aluih. This method is based on consideration of the suitability of the research form with the research objectives. The research instrument was carried out by means of a documentation study. Documentation study was conducted on the folklore of Saba Nan Aluih with an analysis approach to the value of struggle and moral values. From the results of this study, it can be found the results of research on the value of struggle in terms of, the value of self-sacrifice, the value of unity, the value of respect, the value of sabra and unyielding spirit, and the value of cooperation. Based on moral values, moral values ​​in human relations with oneself are divided into, responsibility for education. The moral values ​​of human relations with other humans are divided into, parental advice to children, advice between friends, parental love for children, and child affection for parents.